2018
DOI: 10.1177/1535370218817503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen-like plant compounds on the vaginal epithelium pituitary, adrenal glands, and uterus of rats

Abstract: Plant species with recognized estrogenic activity and widely used by Brazil’s female population to prevent the unpleasant symptoms of menopause were investigated in this work to demonstrate if constituents of taro-inhame ( Colocasia esculenta), cumaru ( Dipteryx odorata), and camapu ( Physalis angulata) have the ability to mimic or interfere with the action of estrogens. Moreover, their potential use as natural sources of estrogen-like substances for hormone replacement therapy was evaluated. (a) In vivo pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Colocasia esculenta fraction also induced hypertrophy of the uterus and pituitary in ovariectomized rats similar to estradiol, mediated by binding with selective estrogenic receptors present in each organ. The overall findings of this study indicated that C. esculenta flavonoid glycoside-rich fraction mimics the action of estrogens, with reduced harmful effects on specific tissues [30] .…”
Section: Estrogenic Activitymentioning
confidence: 63%
“…Colocasia esculenta fraction also induced hypertrophy of the uterus and pituitary in ovariectomized rats similar to estradiol, mediated by binding with selective estrogenic receptors present in each organ. The overall findings of this study indicated that C. esculenta flavonoid glycoside-rich fraction mimics the action of estrogens, with reduced harmful effects on specific tissues [30] .…”
Section: Estrogenic Activitymentioning
confidence: 63%
“…(Euphorbiaceae) showed sperm count boosting effect 21 . While estrogen like activity has been reported in the female 22 , the effect on the male has not been carried out and this has necessitated this study.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens as essential steroid hormones, are secreted mainly from the ovary and placenta and have indispensable roles in women’s reproductive development. It affects the proliferation, differentiation, and physiological tasks of reproductive organs, including the urinary tract, oviduct, mammary gland, and vagina ( Mc Rodrigues et al, 2018 ). Estrogen is also responsible for performing a significant role in non-reproductive organs such as the immune, skeletal, cardiovascular, and nervous systems ( Ikeda et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of reports claim that inflammation can increase during menopause due to declining estrogen level ( Au et al, 2016 ; Skoczek-Rubińska et al, 2021 ). To minimize menopausal complications, the use of synthetic hormones (estrogen or progesterone) that imitate the function of endogenous hormones has become a priority since the 1970s ( Mc Rodrigues et al, 2018 ). Estrogen interacts with two types of estrogen receptors (ERα and ERβ) to exert its beneficial biological effects ( Kim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%